Basic training for population for the first aid training by students rescue team - A. A. Kolodkin; L. I. Dezhurny; S. N. Linchenko; V. I. Starchenko; D. V. Puchnyak (Кубанский научный медицинский вестник, 2015)
The article describes the experience of training the members of students rescue team and the first aid instructors. Conclusions about targeted audience which are the most in need in first aid training and about worries that need to be attended in the system of rendering first aid to the population.